SIMILAR CONCEPT OF DJINN FOUND IN NOVEL BARTIMAEUS: THE AMULET OF SAMARKAND AND IN OLD MALAY LITERATURE: THE TALE OF TAMIM AD-DARI - Hendro Kuncoro (Jurnal Ilmiah Spectral, 2020)
Bartimaeus:The Amulet of Samarkand is a fantasy fiction novel written by Jonathan Stroud, a British author. In this novel Stroud portrayed the Djinn as an enslaved demon from the perspective of a Djinn character named Bartimaeus. This study was conduct to compare the concept of Djinn found in the novel with the concept of Djinn in Indonesian culture because while reading it for the very first time, the writer felt similarity between those conceptions. Meanwhile, the concept of Djinn in Indonesian culture was formed one of them by the arrival of Islam which had an influence on the development of literature in Indonesia. Among them is the Hikayat/Tale of Tamim Ad-Dari. The conception of the Djinn that can be revealed from the comparison of these two literatures are in the form of aspects of the life of the Djinn, its physical description, its abilities, its diversity, its interaction with humans, and creatures related to the Djinn. A comparative literature is what this study concerns. By comparing two things we will comprehend the contents of these two things. This research is qualitative and descriptive. Literature is not only covers the story, but also express the culture and thought of the author that conveyed through the work he has made. Meanwhile culture is a beliefs, system of language, communication, and practices that share in a certain group of peoples which they use to define their identity. Therefore, it can be said that comparative literature facilitate the cross-cultural and interdisciplinary study of literature. And so, this study emphasis on the analysis of social and cultural production within the cultural differences. Hopefully, this study will have pedagogical benefits from the point of view of two cultures presented, which underlines social and cultural aspect of two cultures for student of literature and also for the further research in the field